Layer-by-layer deposition of antimicrobial polymers on cellulosic fibers: a new strategy to develop bioactive textiles - Gomes, Ana (2022)
In recent years, there has been an increase of infectious diseases caused by different microorganisms and the development of antibiotic resistance. In this way, the search for new and efficient antibacterial materials is imperative. The main polysaccharides currently used in the biomedical and pharmaceutical domains are chitin and its derivative chitosan (CH) and alginates (ALG). In this study, a simple technique of Layer by Layer (LbL) of applying polycation CH and polyanion ALG was used to prepare CH/ALG multilayers on cotton samples via the electrostatic assembly with success. The CH/ALG cotton samples (functionalized) were investigated for their antibacterial properties towards Staphylococcus aureus and Klebsiella pneumonia using the international standard method JIS L 1902:2002. The antibacterial activity of the functionalized samples was tested in terms of bacteriostatic and bactericidal activity, and results showed that the samples exhibited a bacteriostatic effect on the two bacteria tested, as expected. In addition, samples with five layers (CH/ALG/CH/ALG/CH) were more effective in inhibiting bacterial growth. This new coating for cellulosic fibers is a new strategy and may open new avenues for the development of antimicrobial polymers with potential application in health-care field.